The last one at the wedding : a novel - Rekulak, Jason (Flatiron Books, 2024)
"From the bestselling author of Hidden Pictures comes a breathtaking work of suspense about a father trying to save his daughter from a life-altering decision that will put everything he loves on the line. Frank Szatowski is shocked when his daughter, Maggie, calls him for the first time in three years. He was convinced that their estrangement would become permanent. He's even more surprised when she invites him to her upcoming wedding in New Hampshire. Frank is ecstatic, and determined to finally make things right. He arrives to find that the wedding is at a private estate-very secluded, very luxurious, very much out of his league. It seems that Maggie failed to mention that she's marrying Aidan Gardner, the son of a famous tech billionaire. Feeling desperately out of place, Frank focuses on reconnecting with Maggie and getting to know her new family. But it's difficult: Aidan is withdrawn and evasive; Maggie doesn't seem to have time for him; and he finds that the locals are disturbingly hostile to the Gardners. Frank needs to know more about this family his daughter is marrying into, but if he pushes too hard, he could lose Maggie forever. An edge-of-your-seat thriller that delves deep into the heart of one family, The Last One at the Wedding is a work of brilliant suspense from a true modern master"--